PENINGKATAN KEMAMPUAN PENGELOLAAN KELAS DAN PENILAIAN PROSES DENGAN PELATIHAN MICRO TEACHING BAGI GURU DI SDN 10 SUNGAI LIMAU - Rasmi Rasmi (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on observations made by researchers at SDN 10 Sungai Limau, it was found that the ability of Classroom Management and Process Assessment with Micro-teaching training for teachers is still low. The purpose of this study was to describe and obtain information on Improving the Ability of Class Management and Process Assessment. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects were 7 teachers of SDN 10 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results show that with Micro Training can improve the ability of Classroom Management and Process Assessment with Micro Training for teachers in SDN 10 Sungai Limau. This is evidenced by the existence of Micro Training training to improve the ability of Classroom Management and Process Assessment with Micro Training for teachers in SDN 10 Sungai Limau from cycle I to cycle II. Teachers' average ability in classroom management and process assessment through micro teaching training in terms of aspect assessment in cycle I is 54.46 in enough category whereas the dimension assessment is in the category with enough category with the value of 59.15 and on appraisal aspect for cycle II is 86.83 With Good category and also on dimensional appraisal for cycle II is 84.82 with Good category.Key Words: Classroom Management Skills and Process Assessment, Micro-training teaching.